Exploring Nursing Students’ Intention To Use Artificial Intelligence: A Mixed-Methods Study Based On Technology Acceptance Model And Theory Of Planned Behavior - Adzim, Moch. Rizqilah Safiil; Amirudin, Mohammad; Wulandari, Siti; Winata, Rafi Hadi; Rias., M.Kep., PhD, Yohanes Andy (Sahabat Publikasi Kuu, 2025)
Background: Artificial intelligence (AI) has the potential to revolutionize nursing practice services. It is important for nurse education to prepare nursing students to utilize AI technology and be willing to adopt it in nursing learning practices. Purpose: The objectives of this study were (1) to explore the relationship between attitudes, perceived utilization and barriers to nursing students' intentions toward AI in the context of nursing practice; (2) to explore nursing students' intentions toward AI in the context of nursing practice in terms of the theory of technology acceptance model and theory of planned behaviors Methods: The study design used a mixed methods approach. A total of 581 nursing students from nursing education institutions in East Java were included in this study. Person correlation, t-test, linear regression and mediation analyses were conducted using Hayes' PROCESS macro in SPSS (Model 4). Focus group discussions were conducted and analyzed verbatim using thematic analysis. Results: Perceived utilization, management of barriers and attitudes toward using AI in nursing practice had a significant positive influence on student nurses' intentions toward AI. Attitude toward AI partially mediated the relationship between perceived utilization and barriers of AI in nursing practice and intention to adopt AI technology. Three overarching themes included (1) AI acceptance; (2) moral-ethics; (3) learning and practice. Conclusions: This study provide insights into the factors in increasing intention to use AI technology. Attitude is a mediating factor that needs to be further developed and analyzed. Nursing stakeholders should implement curriculum policies that emphasize AI acceptance, moral-ethics, and learning and practice. Keywords: Artificial intelligence, attitudes, barriers, intentions, utilization.